2016
DOI: 10.1016/j.jfa.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Freeness and the transposes of unitarily invariant random matrices

Abstract: We show that real second order freeness appears in the study of Haar unitary and unitarily invariant random matrices when transposes are also considered. In particular we obtain the unexpected result that a unitarily invariant random matrix will be asymptotically free from its transpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 15 publications
(9 reference statements)
2
37
0
Order By: Relevance
“…TrA k (B † ) m , vanish in the limit N → ∞. A recent unexpected result of Mingo and Popa [35] concerning Haar random unitary matrices states that U and U T are asymptotically free, and in order to substantiate our interpretation of the convergence to the Marchenko-Pastur distribution in Appendix A we compute numerically the averaged traces of products of two random matrices for the cases of interest discussed throughout our paper. Our results allow us to advance the following Conjecture 3.…”
Section: Unitary Gates Of Size Nxnmentioning
confidence: 89%
“…TrA k (B † ) m , vanish in the limit N → ∞. A recent unexpected result of Mingo and Popa [35] concerning Haar random unitary matrices states that U and U T are asymptotically free, and in order to substantiate our interpretation of the convergence to the Marchenko-Pastur distribution in Appendix A we compute numerically the averaged traces of products of two random matrices for the cases of interest discussed throughout our paper. Our results allow us to advance the following Conjecture 3.…”
Section: Unitary Gates Of Size Nxnmentioning
confidence: 89%
“…For many eigenvalue results there is no distinction between the real and complex case. In [9] we showed that when it comes to freeness there is a difference, in particular with respect to the behaviour of the transpose. In this paper we show that with the partial transpose we continue to see a difference between the real and complex cases.…”
Section: Notation and Statement Of Resultsmentioning
confidence: 95%
“…Since W is unitarily invariant, a consequence of the results from [9] is that W and W T are asymptotically free if d 1 d 2 → ∞. In this section we will present the main results of the paper, which, using the relation form Theorem 9, gives an improvement of the result mentioned above.…”
Section: Asymptotic Freenessmentioning
confidence: 91%
See 1 more Smart Citation
“…i l i l+1 : l ∈ B} satisfy the conditions from Theorem 3.4. Henceforth, if σ ∧ ω( − → k ) is not − → ξ -alternating, equation (7) gives…”
Section: 4mentioning
confidence: 99%